The relationship of the systemic immune inflammation index to severity in chronic spontaneous urticaria - Kalkan, Fikriye; Yesillik, Sait; Demirel, Fevzi; Sonmez, Ezgi; Balaban, Yasemin Akgul; Ilker Inan, Mustafa; Kartal, Ozgur (Biomedical papers, 2025)
Background and aims. Chronic spontaneous urticaria (CSU) is a skin condition causing red, raised, itchy and sometimes painful hives which lasts longer than six weeks. While the cause is unclear, the Urticaria Activity Score-7 (UAS-7), can help to determine the severity of the disease while the Systemic Immune Inflammation Index (SII) defined as neutrophils * platelets/lymphocytes, is a recent marker that shows the inflammatory and immune status and can be easily calculated from routine blood tests using neutrophil, lymphocyte, and platelet counts. We aimed to determine whether the SII correlates with UAS-7 in CSU patients.Methods. We conducted this study on 245 patients with CSU. The UAS-7 score was obtained from all patients. Four groups were generated according to the UAS-7 score as ≤6, 7-15, 16-27, and 28-42. The correlation between the UAS-7 score and SII was evaluated.Results. There was a statistically significant difference between the groups in terms of white blood cell count, neutrophil count, platelet count, Neutrophil-lymphocyte ratio (NLR), Platelet- lymphocyte ratio (PLR), and SII (P<0.05). A positive correlation was found between SII, NLR and PLR, and UAS-7 score. The strongest correlation was between SII and UAS-7, with P<0.001, r=0.642.Conclusion. SII, which is easy to calculate, practical, and objective can be used for predicting the severity of the urticaria and for guiding the follow-up and treatment of these patients.
Keywords: systemic immune inflammation index; chronic spontaneous urticaria; UAS-7 score